PERKEMBANGAN KUMBANG KOKSI Cheilomenes sexmaculata F. (Coleoptera: Coccinellidae) DENGAN INTRODUKSI POLEN SEBAGAI PAKAN ALTERNATIF PENGGANTI Aphis craccivora K. (Homoptera: Aphididae) - , YHONE ARIALISTYA, Drs. Ignatius Sudaryadi, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research on the development of ladybug Cheilomenes sexmaculata F. with the introduction of bee pollen as an alternative diet to subtitute Aphis craccivora K. Cheilomenes sexmaculata F. are predators that are capable of controlling crop pests and have a wide range of feed. So with the introduction of bee pollen is expected can implemented mass rearing, to make biological control agent of cultivated plants pest. The research was conducted in July - December 2013 in the Laboratory of Entomology, Faculty of Biology UGM. The research was conducted with the capture and identification of Cheilomenes sexmaculata F. Then Aphis craccivora K. also captured as natural diet. Rearing of ladybug begins with taking natural diet, followed by a mixture of natural forage feed bee pollen. Then just given feed with bee pollen diet. The data results are presented in life table, then analyzed and calculated value of R to determine the stability of the population. Calculated percentage of survival rate, and the percentage of eggs hatching. Observed the influence of environmental parameters on the development ladybug. Analyzed using One Way Anova to see the real difference between treatments of diet variation. The results of the research showed that there is a significant difference between treatment of bee pollen diet with Aphis craccivora K. diet or mixture diet. Pure bee pollen diet is not able to fulfill the needs of life and the development of ladybug Cheilomenes sexmaculata F. Appointed by the percentage of survival rate of 33.845% for Aphis craccivora K. as natural diet, reaching 13.661% for the mixture diet, and 0% for bee pollen diet. Key Words : Cheilomenes sexmaculata F., Aphis craccivora K., bee pollen, diet variation.